Improving nutrition in Nagaland: Insights from examining trends in outcomes, determinants and interventions between 2006 and 2016 - Kohli, Neha; Nguyen, Phuong Hong; Avula, Rasmi; Tran, Lan Mai; Menon, Purnima (International Food Policy Research Institute, 2017)
The purpose of this Policy Note is to examine the trends in undernutrition in Nagaland and to document trends and geographic variability in the major determinants of nutrition and the coverage of key nutrition and health interventions. In doing this analysis, we aim to highlight the key areas of action to improve nutrition in Nagaland.